
计算:(1)18-(-24)÷(-4);(2)(-2) 2 -|-7|+3-2×(- 1 2 );(3)-1-「-1+(1-0.
计算:(1)18-(-24)÷(-4);(2)(-2)2-|-7|+3-2×(-12);(3)-1-「-1+(1-0.5×23)」;(4)-3xy-(2xy-5xy);(...
计算:(1)18-(-24)÷(-4);(2)(-2) 2 -|-7|+3-2×(- 1 2 );(3)-1-「-1+(1-0.5×2 3 )」;(4)-3xy-(2xy-5xy);(5)3(5a+4)-(3a-10);(6)先化简,再求值:(6a 2 +4ab)-2(3a 2 +ab- 1 2 b 2 ),其中a=2,b=1.
展开
展开全部
(1)原式=18-6=12; (2)原式=4-7+3+1=1; (3)原式=-1-[-1+1-4]=-1+4=3; (4)原式=-3xy-2xy+5xy=0; (5)原式=15a+12-3a+10=12a+22; (6)原式=6a 2 +4ab-6a 2 -2ab+b 2 =2ab+b 2 , 当a=2,b=1时,原式=2×2×1+1=5. |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询